Remote working and wellbeing of the female academicians during the COVID-19 Movement Control Order enforcement (MCO) in Malaysia - Minhat, Halimatus Sakdiah (Persatuan Pakar Perubatan Kesihatan Awam Malaysia, Malaysian Public Health Physicians Association, 2024)
The enforcement of movement control order to curb the highly transmissible COVID-19 infection causes numerous transitions in daily life activities, which include the practice of remote working. Identifying the predictors of Malaysian female academician general wellbeing was the main goal of this study. Eligible female academicians were recruited from a public university in Malaysia, using the stratified proportionate to size probability sampling from April to June 2021, who were working from home for the first time during the COVID-19 pandemic. Variables included in the study were organised according to the constructs of the socioecological model. Data was collected using a pre-tested online questionnaire, with Cronbach alpha values between 0.712 and 0.899. A total of 172 female academicians participated in this study. The proportion of respondents with positive general wellbeing were approximately 50%, with those age range between 41 and 45 years old and working remotely several times per week predicted to have 6.491 (95% CI: 1.132; 37.235) and 8.999 (95% CI: 1.161; 69.769) odds of having positive wellbeing. Meanwhile, female academicians who had poor work-life balance and experienced professional isolation had 78% and 70% less likelihood of having positive wellbeing. Early identification of female academicians at risk of work-life imbalance and professional isolation is necessary, particularly those younger to prevent deterioration of wellbeing while working from home.